The New Old-Timers. - Davis, Wes (Southwest Review, 2010)
In this article the author reflects on the popularity of the banjo. He discusses the banjo in popular culture as well as various historical stereotypes associated with banjos and banjo players. He explores the roots of banjo playing in southern Appalachian states and stereotypes associated with impoverished rural communities. The author discusses the role of the banjo in his relationship with his father, the band Flatt and Scruggs, and instructional banjo workshops.